Clinicopathological features and oncological outcomes of patients with young-onset rectal cancer. Issue 5 (9th March 2020) - Zaborowski, A M; Murphy, B; Creavin, B; Rogers, A C; Kennelly, R; Hanly, A; Martin, S T; O'Connell, P R; Sheahan, K; Winter, D C
Abstract: Background: The incidence of rectal cancer among adults aged less than 50 years is rising. Survival data are limited and conflicting, and the oncological benefit of standard neoadjuvant and adjuvant therapies is unclear. Methods: Disease-specific outcomes of patients diagnosed with rectal cancer undergoing surgical resection with curative intent between 2006 and 2016 were analysed. Results: A total of 797 patients with rectal cancer were identified, of whom 685 had surgery with curative intent. Seventy patients were younger than 50 years and 615 were aged 50 years or more. Clinical stage did not differ between the two age groups. Patients aged less than 50 years were more likely to have microsatellite instability (9 versus 1·6 per cent; P = 0·003) and Lynch syndrome (7 versus 0 per cent; P < 0·001). Younger patients were also more likely to receive neoadjuvant chemoradiotherapy (67 versus 53·3 per cent; P = 0·003) and adjuvant chemotherapy (41 versus 24·2 per cent; P = 0·006). Five-year overall survival was better in those under 50 years old (80 versus 72 per cent; P = 0·013). The 5-year disease-free survival rate was 81 per cent in both age groups ( P = 0·711). There were no significant differences in the development of locoregional recurrence or distant metastases. Conclusion: Despite accessing more treatment, young patients have disease-specific outcomes comparable to those of their older counterparts. Graphical Abstract: A total of 685 patients with rectal cancer who underwent surgery with curative intent were analysed. Seventy were aged under 50 years and 615 were aged 50 years or over. Younger patients displayed short- and long-term disease-specific survival comparable to that of their older counterparts despite receiving more neoadjuvant and adjuvant therapy. More aggressive treatment, similar survival